Desorganização, oportunidade e crime : uma análise "ecológica" dos homicídios em Belo Horizonte - Braulio Figueiredo Alves da Silva (2012)
The study of "places" has recently received special attention as a research topic in contemporary criminology. To understand the variation of violence across space, realizing the interrelations between structural properties of "ecological units" and the distribution of crime has promoted the improvement of the theories and the development of methodological tools that expand our knowledge about the spatial and temporal dynamics of the phenomenon. The tradition of "ecological studies" stemmed from the work of the Chicago School associates factors such as residential mobility, ethnic/racial heterogeneity and economic deprivation to the community context of social disorganization, which in turn prevents the effective control at local level. When the importance of the circumstances in which crimes occur are emphasized, the perspective of routine activities presents a relevant explanation of how and to what extent the convergence of offenders, victims and places that determine a particular context of criminal opportunity occur. This study aims to give continuity to the efforts of research that suggest the merger of the Social Disorganization and Routine Activities Theories to explain the potential for crime of certain places. Among the few studies that present a proposal of integration these approaches, is the Multicontextual Criminal Opportunity Theory drafted Pamela Wilcox and her colleagues. We based our work on this study and tried to evaluate the relationship between the community mechanisms of social control and levels of violence. In particular, we analyzed spatial and temporal dynamics of homicides in the city of Belo Horizonte and identified a spatial pattern that is not random. We used the census tracts as units of analysis, and built measures representing the community dimension of social disorganization and criminal opportunity to assess their direct effect on homicide rates in these areas. Then we analyzed this relationship mediated by the community elements of social control. It was observed that the construct of guardianship represented by the community perception of trust and effectiveness in the police institutions is a crucial element in the activation of community mechanisms of systemic control and collective efficacy. In the context of this study, it was found that the institutional connection boosts the community dimension of informal control and mutual trust forming a local protection against crime similar to the guardianship element of routine activities approach.